A promising dual mode SPECT/CT imaging platform based on 99mTc-labeled multifunctional dendrimer-entrapped gold nanoparticles. Issue 21 (19th May 2017) - Wen, Shihui; Zhao, Lingzhou; Zhao, Qinghua; Li, Du; Liu, Changcun; Yu, Zhibo; Shen, Mingwu; Majoral, Jean-Pierre; Mignani, Serge; Zhao, Jinhua; Shi, Xiangyang
Abstract : Multifunctional 99m Tc-labeled dendrimer-entrapped gold nanoparticles modified with different surface groups can be used for preferential SPECT/CT imaging of different organs. Abstract : Multifunctional 99m Tc-labeled dendrimer-entrapped gold nanoparticles ( 99m Tc-Au DENPs) were designed and synthesized. Our results show that the type of surface groups (acetyl or hydroxyl) significantly impact the biodistribution profile of the 99m Tc-Au DENPs, thereby allowing for preferential SPECT/CT imaging of different organs.